UJI PRAKTIKALITAS PEMBELAJARAN BERBASIS GIM EDUKASI MENGGUNAKAN GDEVELOP PADA MATA PELAJARAN IPA DI SEKOLAH DASAR - Susalti Nur Arsyad; Ahmad Swandi; Yulia Nurmasita Devi; Sri Rahmadhanningsih; Arief Fauzan; Andi Hamzah Fansury (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research was conducted to find out how to practice science learning for elementary school students using educational games that have been developed with the Gdevelop application. This goal is based on the stigma in the form of public perception that games have a negative impact on learning, as well as a lack of knowledge about using games or other digital learning tools in the classroom, which causes students to become more accustomed to learning using conventional teaching techniques. This research was conducted using a qualitative descriptive method, and the instruments used were questionnaires and interviews using the data analysis technique of Miles and Huberman's model (Analysis Interactive Model). This research was conducted at SDN Lariang Bangi I, the number of respondents in this study were 23 students. The practicality of educational games is determined based on product trials and the responses of teachers and students to educational games. The results of this study indicate that there are (83%) students who agree that the use of educational games as learning media can make it easier for them to understand science learning material. In addition, based on the validation results, it shows that the teacher's assessment of the product is above 80% which indicates that the product is suitable for use in learning. From the results of the research that has been done, it can be concluded that the use of educational games based on Gdevelop is considered very practical in its use.